Overexpansion of the 29 mm SAPIEN 3 transcatheter heart valve in patients with large aortic annuli (area > 683 mm2): A case series. Issue 6 (24th August 2017) - Mathur, Moses; McCabe, James M.; Aldea, Gabriel; Pal, Jay; Don, Creighton W.
Abstract: Objectives: To evaluate overexpanded 29 mm SAPIEN (S3) transcatheter heart valves in patients with aortic annuli area >683 mm 2 . Background: The largest valve area the 29 mm S3 is specified for is 683 mm 2 . Valve overexpansion has been performed in patients with larger aortic annuli, but data are limited. Moreover, feasibility in areas >740 mm 2 is unknown. Methods: All 29 mm S3 transcatheter aortic valve replacements (TAVR) at a single center over 23‐months were retrospectively reviewed. Patients with annulus areas >683 mm 2 were included. Immediate post‐TAVR hemodynamics and transthoracic echocardiography (TTE) findings on post‐TAVR day‐1 and day‐30 were recorded. Results: Of 81 29 mm S3 TAVR cases, 3 (3.7%) met inclusion criteria (patients 1, 2, and 3 had CT‐scan derived areas of 748.1 mm 2, 793 mm 2, and 787 mm 2, respectively). Annular eccentricity index ranged from 0.12 to 0.25. All underwent transfemoral TAVR with 29 mm S3 valves overexpanded using +4 mL of contrast. Post‐dilatation with +5 mL was performed in patient 2. The average valve shortening was 10.68 mm. On day 1, patients 1 and 2 had trace and mild paravalvular leak (PVL) (respectively), whereas, patient 3 had mild–moderate PVL. Patient 1 was also noted to have trace central AR on day 1. No other central AR was noted. Immediate post‐procedure aortic regurgitation (AR) index in patients 1, 2, and 3 was 43, 34, and 33 respectively. At 30 days, AR was completely resolved in patient 1, whereas AR severity in patients 2 and 3 remained similar. No patients had > moderate AR at any point during follow‐up. No valve migration or embolization occurred. Patient 1 required a permanent pacemaker. No other major complications were noted. All patients were clinically stable at 30 days. Conclusions: TAVR using overexpanded 29 mm S3 in valve areas >740 mm 2 (up to 793 mm 2 ) seemed to be safe and feasible in our small series. Further study in a larger series is needed to determine clinical outcomes in this patient population.